Impact of tillage and no-tillage cultivation on the occurrence of entomopathogenic fungi in soil with integrated plant protection - Roman Kierzek; Danuta Sosnowska; Agata Pruciak-Nowak (Journal of Plant Protection Research)
This study aimed to evaluate the impact of tillage and no-tillage cultivation on entomopathogenic fungi in the soil. The research was carried out in 2021‒2022 on plots at the Field Experimental Station of the Institute of Plant Protection – National Research Institute in Winna Góra, Poland. Winter oilseed rape, pea and winter wheat were grown on the plots. Entomopathogenic fungi were isolated using the trapping insect method and their occurrence intensity was assessed. The results demonstrated a positive effect of no-tillage cultivation on the presence of entomopathogenic fungi in the soil. In May 2021, the greatest numbers of trapped insect larvae infected by fungi were in the pea plots (90%) with no-tillage systems, while with tillage it was 43% lower. In June 2022, the greatest number of larvae infected by fungi were in the pea plots (96.7%) with no-tillage systems, while with tillage it was 23% lower. Among the isolated entomopathogenic fungi, the dominant genus was Cordyceps in all cultivation technologies.